2000
DOI: 10.1073/pnas.97.14.7927
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of human Rad18 results in defective postreplication repair and hypersensitivity to multiple mutagens

Abstract: Postreplication repair functions in gap-filling of a daughter strand on replication of damaged DNA. The yeast Saccharomyces cerevisiae Rad18 protein plays a pivotal role in the process together with the Rad6 protein. Here, we have cloned a human homologue of RAD18, hRAD18. It maps on chromosome 3p24 -25, where deletions are often found in lung, breast, ovary, and testis cancers. In vivo, hRad18 protein binds to hHR6 protein through a conserved ring-finger motif. Stable transformants with hRad18 mutated in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 22 publications
8
133
1
1
Order By: Relevance
“…However, the possibility that hRad18 titrates the human homologues of Rad6 is unlikely since it has been reported that the RING finger of hRad18 is necessary for hRad6A/B-hRad18 binding (34). Our deletion analysis showed that the RING finger motif does not play an essential role in the interaction between hRad18 and HIV-1 integrase, ruling out a direct competition between HIV-1 integrase and hRad6A/B for hRad18 binding.…”
Section: Discussionmentioning
confidence: 79%
“…However, the possibility that hRad18 titrates the human homologues of Rad6 is unlikely since it has been reported that the RING finger of hRad18 is necessary for hRad6A/B-hRad18 binding (34). Our deletion analysis showed that the RING finger motif does not play an essential role in the interaction between hRad18 and HIV-1 integrase, ruling out a direct competition between HIV-1 integrase and hRad6A/B for hRad18 binding.…”
Section: Discussionmentioning
confidence: 79%
“…Genetic studies of Saccharomyces cerevisiae suggest that all known components of TLS belong to the epistasis group of the RAD6-RAD18 genes (21,22), which are conserved from yeast to mammalian cells (23)(24)(25)(26)(27). The Rad6 protein is one of the ubiquitin-conjugating enzymes (E2s) and forms a tight complex with the Rad18 protein, which may have E3 ubiquitin ligase activity (28,29 lymphocyte line DT40 (30).…”
mentioning
confidence: 99%
“…Mouse and human Rad18 are able to interact with both HR6A and HR6B protein (Tateishi et al, 2000;Xin et al, 2000). As in budding yeast, disruption of RAD18 in human cells or in DT40 chicken lymphocyte results in sensitivity to a variety of DNA-damaging agents (Yamashita et al, 2002).…”
Section: Rad18mentioning
confidence: 99%